Current understanding of plant Polycomb group proteins and the repressive histone H3 Lysine 27 trimethylation. (29th July 2020) - Jiao, Huijun; Xie, Yuanyuan; Li, Zicong
Abstract : Polycomb group (PcG) proteins are highly conserved chromatin-modifying complexes that implement gene silencing in higher eukaryotes. Thousands of genes and multiple developmental processes are regulated by PcG proteins. As the first chromatin modifier been identified in model plant Arabidopsis thaliana, the methyltransferase CURLY LEAF (CLF) and its catalyzed histone H3 Lysine 27 trimethylation (H3K27me3) have already become well-established paradigm in plant epigenetic study. Like in animals, PcG proteins mediate plant development and repress homeotic gene expression by antagonizing with trithorax group proteins. Recent researches have advanced our understanding on plant PcG proteins, including the plant-specific components of these well-conserved protein complexes, the close association with transcription factors and noncoding RNA for the spatial and temporal specificity, the dynamic regulation of the repressive mark H3K27me3 and the PcG-mediated chromatin conformation alterations in gene expression. In this review, we will summarize the molecular mechanisms of PcG-implemented gene repression and the relationship between H3K27me3 and another repressive mark histone H2A Lysine 121 mono-ubiquitination (H2A121ub) will also be discussed.